Numerical Investigation of the Clocking Effect on the Centrifugal Pump as Turbine. Issue 1 (March 2021) - Jiang, W; Liu, Z L; Wang, Y C; Yang, J G; Hou, G Y
Abstract: The clocking effect is widely recognized to have an important impact on the function of rotating machinery. The effect of the clocking position on the flow field and the hydraulic performance in a pump as turbine (PAT)with vane diffusers has been investigated and analyzed numerically. The results show the hydraulic performance of the PAT decreasing gradually as the diffuser blade near the tongue. Under optimal operating conditions, the maximum difference in efficiency for different guide vane positions is 2.2%. When the position of the tongue is equidistant from the two diffuser blades, the energy loss of the volute and the diffuser is minimized. And the flow field results prove that the timing position affects the flow field in the volute and diffuser to a certain extent, but has little effect on the impeller. In addition, this may provide ideas for the installation of PAT with guide vanes, and the diaphragm should be as far away as possible from the two adjacent diffuser blades.